Classic polyarteritis nodosa presenting initially as a case of cutaneous polyarteritis nodosa: A case report - Adhikari, Sabina (Asian Journal of Medical Sciences, 2024)
Classic polyarteritis nodosa (PAN) is an uncommon form of aggressive systemic vasculitis involving small-to-medium sized arteries usually of renal vasculature and other visceral organs but characteristically sparing the lung vasculature. Cutaneous PAN (c-PAN) is still a rare type of small-to-medium vessel vasculitis with involvement of skin without any systemic or visceral involvement. However, extracutaneous features such as arthritis, arthralgia, myopathy, and myositis can co-exist with the cutaneous features. c-PAN can be confirmed histopathologically by the presence of polymorphonuclear leukocytes around the medium-sized vessels with evidence of fibrinoid necrosis and luminal thrombi at the bifurcations. While c-PAN has a benign but chronic course and can be managed with low doses of short-course oral steroids or anti-inflammatory drugs, systemic involvement has an aggressive course and needs adequate and prompt immunosuppression with high dose oral steroids, cyclophosphamide, rituximab, or other immunosuppressive. We present a case of a 33-year-old male who landed in our OPD with features of c-PAN and on further investigative workup was found to have a renal infarct.